»Tegobe« gob: Demistifikacija gliv v okviru okoljske komunikacije - Bojan Varga, Bojan Varga (Komuniciranje okoljske krize, 2025)
Fungi hold remarkable potential in addressing environmental challenges – from mycoremediation (i.e. the cleanup of polluted areas with fungi) and the development of sustainable materials to the degradation of plastic – yet remain largely underrecognized in practice. Their marginal presence in environmental discourse is not only due to scientific complexity, but also to cultural and communicative factors. One such factor is mystification – fungi are often perceived by the public as dangerous, mysterious, or insignificant. This study examines how natural and social factors influence public understanding of fungi and explores how interdisciplinary approaches can foster more effective awareness. Based on interviews with actors engaged in fungal research, cultivation, and/or environmental education in Slovenia, the study identifies key communication obstacles. Insights into their practices reveal a lack of social science perspectives but also point to the potential for developing new, more integrated approaches to environmental communication and open avenues for further research.